PENINGKATAN MOTIVASI BELAJAR, KEAKTIFAN BELAJAR, DAN HASIL BELAJAR IPS MELALUI MODEL PEMBELAJARAN BLENDED LEARNING BERBANTUAN E-MODULE - Novianto, Victor; Purwanti, Anna Dwi (Jurnal Sosialita, 2024)
This study aims to find out how the application of the blended learning model assisted by E-module can increase learning motivation, learning activity, and learning outcomes for social studies subject matter in fifth grade students at SDN Belang Patuk in 2021/2022. This type of research is Classroom Action Research with two cycles, each cycle consisting of planning, implementation, observation, and reflection. The research subjects were students of class V SDN Belang Patuk with a total of 21 students consisting of 12 male students and 9 female students. The data analysis technique in this study used qualitative analysis techniques on the results of observations and questionnaires, and quantitative analysis on the results of students' scores. The results showed that the application of the blended learning model assisted by E-module made the learning atmosphere fun and there was an increase in learning motivation, learning activity, and student learning outcomes, namely from pre-cycle conditions, cycle I to cycle II. In the pre-cycle, the percentage of students' learning motivation in the high category was 47.62%, in the first cycle it rose to 71.43% and in the second cycle it rose to 85.71%. While in the pre-cycle the percentage of student learning activity in the high category was 52.38%, in the first cycle it rose to 71.43% and in the second cycle it rose to 85.71%. Student learning outcomes also increased, namely in the precycle the percentage of students who completed the KKM was 47.62%, in the first cycle it increased to 71.43%, then increased to 90.48% in the second cycle. It can be concluded that the application of the E-module-assisted blended learning model can increase learning motivation, learning activity, and learning outcomes for social studies subject matter.